A bundle improves eye care in PICU. Issue 9 (27th April 2016) - McCall, Karen; Hussin, Hussin M; Gregory, Maria Elena; Dutton, Gordon; Richardson, Julie
Abstract : Background: Intensive care patients are susceptible to developing painful corneal epithelial deficits. Provision of eye care to prevent deficits was limited in our paediatric intensive care unit (PICU) population. Interventions: A new eye care bundle was introduced, comprising a guideline for eye care, the addition of eye lubricants to the electronic prescribing order set for new admissions to PICU and staff education on the importance of eye care. Weekly examinations over a 2-month period following implementation of the bundle evaluated eye care provision and presence of corneal epithelial deficits on ophthalmic examination. Results: Provision of formal eye care improved from 19% to 96%. The incidence of deficits was lower than previously, simple eye ointment reduced the risk of deficits, even in incompletely closed eyes. Conclusions: Use of an eye care bundle, together with a multidisciplinary team approach to eye care, improves the provision of eye care in PICU.